Sex therapy with religious patients : working with Jewish, Christian, and Muslim communities - Jacobson, Caleb (New York, NY : Routledge, 2024)
"Sex Therapy with Religious Patients is a comprehensive guidebook for mental health professionals who work with those struggling with sexual issues within a religious context. The book provides practical guidance on how to approach sensitive topics related to sex and religion, including addressing religious beliefs and values that may impact sexual behavior, beliefs, and attitudes. Drawing on research and clinical experience, the book offers a range of evidence-based interventions for working with individuals from different Jewish, Christian, and Muslim backgrounds. It also explores the unique challenges and opportunities presented by patients' religious beliefs and provides strategies for integrating spirituality into the therapeutic process. The book is written in an accessible and engaging style, with real-life case examples and exercises that can be used in therapy sessions. It is an essential resource for mental health professionals seeking to enhance their skills in working with religious individuals who are seeking sex therapy"--
Keywords: Sex therapy -- Religious aspects; Sex -- Religious aspects; PSYCHOLOGY / Human Sexuality; PSYCHOLOGY / Psychotherapy / Couples & Family; RELIGION / Sexuality & Gender Studies